Use of Industrial Waste to Produce Ceramic Coatings on Metal - Pereira Antunes, Maria Lucia; Souza, C.S.; Moraes, R.F.; Rangel, E.C.; Cruz, N.C. (European Journal of Sustainable Development, 2019)
Industrial processes are activities that produce large amounts of wastes. Often these wastes are disposed in dam or landfills, occupying large areas and causing environmental damage such as the contamination of water and soil. According to the Circular Economy concept, waste should be minimized and reused as raw material in a new process. This work describes two residues, namely red mud (bauxite residue) and waste foundry sand (WFS), whose chemical compositions indicate their suitability for use as protective coatings. These residues were used to obtain coatings on aluminum alloy by employing plasma electrolytic oxidation (PEO). The PEO process enables the creation of coatings that are durable, uniform, and strongly adherent on metallic components of different shapes. The mineralogical compositions of the coatings were investigated using X-ray diffraction (XRD). Surface wettability was determined by contact angle measurements and evaluation was made of the average surface roughness. Alumina was the main phase observed by XR, indicating good chemical stability and high thermal resistance. The coatings obtained with the red mud were thicker and less rough, compared to those obtained with the WFS. The results demonstrated the feasibility of using these wastes for coating metals in order to improve their properties and enable new applications. Keywords: Industrial Waste, Red Mud, Waste Foundry Sand, Circular Economy, Ceramic Coating.